Golimumab therapy-induced indicators of X-ray inflammation progression and magnitude according to magnetic resonance imaging evidence in patients with rheumatoid arthritis, ankylosing spondylitis, or psoriatic arthritis - Aleksandr Viktorovich Smirnov (Современная ревматология, 2013)
The paper gives data on the progression of X-ray and magnetic resonance imaging changes in the hand and foot joints of patients with rheumatoid arthritis and psoriatic arthropathy and in the axial skeleton of those with ankylosing spondylitis when golimumab is used. Golimumab therapy is shown to retard the progression of structural changes in the peripheral joints and vertebral column. There is a significant correlation between magnetic resonance imaging evidence and blood C-reactive protein concentrations.